Triple-negative breast carcinomas of low malignant potential: review on diagnostic criteria and differential diagnoses - (:unkn) unknown (SPRINGER, 2021)
Triple-negative breast carcinomas constitute a wide spectrum of lesions, mostly being highly aggressive. Nevertheless, some special histologic subtypes can have low malignant potential. The purpose of the present paper is to review diagnostic criteria and prognostic parameters of breast neoplasms of special histotypes. Specifically, adenoid cystic carcinoma, adenomyoepithelioma, acinic cell carcinoma, mucoepidermoid carcinoma, tall cell carcinoma with reverse polarity, and secretory carcinoma will be discussed. For each tumour, definition and morphological and molecular features, together with prognostic parameters, will be presented. Paradigmatic cases will be illustrated.
Keywords: Triple-negative breast carcinoma; Adenoid cystic carcinoma; Adenomyoepithelioma; Acinic cell carcinoma; Mucoepidermoid carcinoma; Tall cell carcinoma with reverse polarity; Secretory carcinoma; ADENOID-CYSTIC CARCINOMA; ACINIC CELL-CARCINOMA; PAPILLARY THYROID-CARCINOMA; GRADE MUCOEPIDERMOID CARCINOMA; NEEDLE-ASPIRATION-CYTOLOGY; GLAND-TYPE TUMORS; COLLAGENOUS SPHERULOSIS; MYOEPITHELIAL CARCINOMA; SECRETORY CARCINOMA; SOLID VARIANT